Strides towards the realization of cure for cartilage defects and osteoarthritis: the limitation and regulatory challenges - Ude Chinedu Cletus,; Azizi Miskon,; Ruszymah Hj. Idrus, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Despite remarkable mechanical durability and strength, hyaline cartilage has very limited capacity for self-repair when injured and over time, may degenerate to osteoarthritis. We evaluated the most significant mile stones attained, in the pursuit of cure for cartilage defects and osteoarthritis. The basic treatment options include: Natural or physical therapy, medications, nutritional supplements, nutriceuticals and chondroprotective agents. Next are repairs and replacements, which include surgical procedures: Debridement/chondroplasty, microfracturing, mosaicplasty, periosteum transplantation, osteochondral autografting and allografting, high tibial osteotomy and total knee arthroplasty. But, current trend has shifted from repair, replacement, to most recently regeneration. Regenerations include the cell and gene therapies. While cell therapy involves the use of cells isolated from different tissues to cause regeneration of cartilage; gene therapy involves the selection of appropriate gene and optimal vector to incorporate cDNA. There has been much positivity reported with big animal models, which has led to several ongoing clinical trials. Translations of these findings hold high promises, though not without inherent regulatory hurdles. Considering the initial success rates, there are increasing hopes of realizing these treatments from bench to bedsides. Significant improvements in the treatment of cartilage degenerations and osteoarthritis have been made so far, but no gold standard delineated.